Building external wall thermal insulation system
By using a building exterior wall insulation system composed of adhesive layer, insulation layer and decorative layer on the exterior wall of the building, and using nanomaterials and wood fibers, the problems of limited insulation effect and dissatisfaction with decorative requirements in the existing technology are solved, and excellent thermal insulation performance and natural decorative effect are achieved.
Patent Information
- Application Number
- CN202411854797.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The insulation effect of existing building exterior wall insulation systems is limited and cannot meet people's requirements for building exterior wall decoration.
The building exterior wall insulation system consisting of an adhesive layer, an insulation layer and a decorative layer is adopted. The insulation layer contains components such as nanoalumina, nanosilica, nanofibers, nanosilver and wood fibers. The decorative layer contains components such as nanoalumina, nanosilica, second hollow microbeads and colored sand. Through the reasonable proportioning and stirring of these components, a good stacking state and bonding strength are formed.
It achieves excellent thermal insulation performance of building exterior walls, and has natural color and decorative effects, enhancing the durability and service life of the insulation system.
Smart Images

Figure BDA0005191528920000101 
Figure BDA0005191528920000102 
Figure BDA0005191528920000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building thermal insulation and energy saving, and in particular relates to a building exterior wall thermal insulation system. Background Art
[0002] External wall insulation is one of the important means of saving energy and protecting the environment. External wall insulation system of buildings improves the thermal insulation performance of building walls and reduces energy loss by coating thermal insulation materials on the surface of building external walls, thereby reducing heating and cooling energy consumption. At the same time, the external wall insulation system can also improve the indoor comfort of buildings, improve the antifreeze performance of walls, and extend the service life of buildings. External wall insulation of buildings has become an important means of energy conservation in buildings. In addition, with the continuous improvement of living standards, people have higher and higher requirements for the decoration of building walls, such as requiring buildings to have natural colors and beautiful appearance.
[0003] The invention patent with authorization announcement number CN 103938740 B discloses a building exterior wall insulation system, which includes an insulation primer coating and an exterior wall insulation base paste. The system achieves building exterior wall insulation by superimposing primer insulation powder in the insulation primer coating and putty insulation powder in the exterior wall insulation base paste, resulting in limited insulation effect and unable to meet people's requirements for the decoration of the building exterior wall. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a building exterior wall thermal insulation system, which has excellent thermal insulation performance and natural color.
[0005] The technical solution of the present invention to solve the above problems is as follows:
[0006] A building exterior wall insulation system, comprising an adhesive layer, an insulation layer and a finishing layer arranged in sequence from the wall surface to the outside of the wall;
[0007] The thermal insulation layer comprises the following components in parts by weight:
[0008] 5-10 parts of nano-alumina, 5-10 parts of nano-silicon dioxide, 2-5 parts of nano-fibers, 5-10 parts of nano-silver, 10-15 parts of wood fibers, 10-20 parts of silicate cement, 2-5 parts of first hollow microspheres, 25-35 parts of first adhesive, 20-35 parts of water, 0.5-1 part of first thickener, 0.5-1 part of first dispersant, 0.5-1 part of first defoamer, 0.5-1 part of first wetting agent, 0.5-1 part of first film-forming aid;
[0009] The first adhesive is selected from at least one of pure acrylic emulsion and styrene acrylic emulsion;
[0010] The finishing layer comprises the following components in parts by weight:
[0011] 2-5 parts of nano silicon dioxide, 2-5 parts of nano aluminum oxide, 10-15 parts of second hollow microspheres, 45-65 parts of colored sand, 25-40 parts of second adhesive, 25-40 parts of water, 0.5-1 part of second defoamer, 0.5-1 part of second dispersant, 0.5-1 part of second film-forming aid, 0.5-1 part of second thickener, 0.5-1 part of second wetting agent;
[0012] The second adhesive is selected from at least one of pure acrylic emulsion and styrene acrylic emulsion.
[0013] The wood fiber is an organic flocculent fiber material obtained by chemical treatment and mechanical processing of natural renewable wood. The pure acrylic emulsion is a dispersion of polyacrylate in water formed by emulsion polymerization or suspension polymerization of one or more acrylate monomers or monomers containing oligomers; the styrene acrylic emulsion is a dispersion of styrene-acrylate copolymer in water formed by emulsion polymerization or suspension polymerization of styrene monomers or monomers containing oligomers and one or more acrylate monomers or monomers containing oligomers.
[0014] Preferably, the adhesive layer comprises the following components in parts by weight:
[0015] 30-40 parts of acrylic emulsion, 45-55 parts of Portland cement, 30-40 parts of quartz sand, 3-5 parts of wood fiber, 40-50 parts of water, 0.5-1.5 parts of the third dispersant, and 0.5-1.5 parts of the third defoamer;
[0016] The acrylic emulsion is selected from at least one of pure acrylic emulsion and styrene acrylic emulsion.
[0017] Preferably, the thickness of the adhesive layer is 0.5-2 mm, the thickness of the thermal insulation layer is 0.8-3 mm, and the thickness of the finishing layer is 0.2-0.5 mm.
[0018] Preferably, the silicate cement in the bonding layer is 42.5 grade ordinary silicate cement; the particle size distribution range of the quartz sand is 0.08-0.80 mm, D50 is 0.25-0.30 mm, and D90 is 0.18-0.40 mm.
[0019] Preferably, the wood fibers in the adhesive layer have a length of 1 to 3 mm and a diameter of 0.05 to 0.1 mm.
[0020] Preferably, the third dispersant in the adhesive layer is selected from at least one of sodium polyphosphate, sodium hexametaphosphate, sodium pyrophosphate and sodium polyacrylate.
[0021] Preferably, the third defoaming agent in the adhesive layer is selected from at least one of a mineral oil defoaming agent and a silicone defoaming agent.
[0022] The method for preparing the adhesive layer comprises the following steps:
[0023] Add the formulated amount of acrylic emulsion into the stirring kettle, stir at 100-200 rpm for 10-15 minutes, then add the formulated amount of silicate cement, quartz sand, wood fiber, water, the third dispersant and the third defoamer into the stirring kettle, stir and disperse at 650-750 rpm for 25-35 minutes to obtain the material for the adhesive layer.
[0024] The building exterior wall thermal insulation system of the present invention can improve the bonding strength between the thermal insulation layer and the building exterior wall by providing an adhesive layer, prevent the thermal insulation layer from falling off and cracking from the building exterior wall, thereby ensuring the thermal insulation effect of the thermal insulation system.
[0025] Preferably, the particle size of the nano-alumina in the thermal insulation layer is 20-100 nm, the particle size of the nano-silicon dioxide is 50-200 nm, and the particle size of the nano-silver is 25-50 nm.
[0026] Preferably, the nanofibers in the thermal insulation layer are nanoceramic fibers, and the diameter of the nanoceramic fibers is 100-300 nm.
[0027] Preferably, the first hollow microspheres in the thermal insulation layer are nano-ceramic hollow microspheres with a particle size of 100 to 500 nm.
[0028] Preferably, the length of the wood fibers in the thermal insulation layer is 0.5-1 mm, and the diameter is 0.02-0.05 mm.
[0029] Nano-alumina has the characteristics of low thermal conductivity and good thermal insulation, and nano-alumina has high reflectivity in the solar spectrum band. Nano-silicon dioxide has high specific surface area and low thermal conductivity, good dispersibility, and extremely strong ultraviolet and infrared reflection characteristics. It can resist ultraviolet aging and thermal aging, and increase the thermal insulation of the insulation layer. Nano-silver is a metal nanoparticle with good biocompatibility and low toxicity. It not only has high infrared reflection efficiency, but also has acid and alkali resistance and high antioxidant stability. It can greatly increase the infrared reflectivity of the insulation layer, thereby improving the thermal insulation effect of the insulation layer. Nanofibers have the characteristics of light weight, high temperature resistance, good thermal stability, low thermal conductivity, low specific heat and resistance to mechanical vibration. Nano-ceramic hollow microspheres can reflect infrared light and invisible light, and their internal hollow structure gives them extremely low thermal conductivity and good thermal insulation.
[0030] The above-mentioned nanomaterials are small in size and large in surface area, so the ratio of surface to volume is high, and the surface interacts strongly with the surrounding substances, which makes the surface activity of the nanomaterials very high, thereby enhancing the heat transfer performance of the insulation layer. And because the surface area of nanomaterials is large, there are a large number of surface defects near the surface of the material. These defects will affect the thermodynamic properties of the nanomaterials, making them have different thermal conductivities at different temperatures, and can quickly respond to and adjust the thermal conductivity of the coating according to changes in ambient temperature. For example: when the temperature is high, surface defects will cause an increase in entropy, thereby causing the heat capacity and thermal conductivity of the nanomaterial to change. The material has a high thermal conductivity, which can speed up the dissipation of indoor heat and keep the room cool; in a low temperature environment, the material has a low thermal conductivity, which can isolate the transfer of indoor heat from the cold air outside and keep the room warm.
[0031] Wood fiber has a large specific surface area, excellent thermal insulation properties, and strong cross-linking function and dimensional stability. After being mixed with the first adhesive and nanomaterials, the fibers are densely overlapped to form a three-dimensional network structure, which enhances the support and durability of the insulation layer, improves the stability of the insulation layer, and prevents the insulation layer from cracking.
[0032] By controlling the particle size and content of the above nanomaterials, they form a better accumulation state in the insulation layer, have a better blocking rate for infrared light and ultraviolet light, and improve the thermal insulation effect. In addition, the nano thermostatic material has special properties such as small size effect and surface effect. After combining with the first adhesive, wood fiber, etc., the insulation layer has the characteristics of high bonding strength and good weather resistance.
[0033] Preferably, the first dispersant is selected from at least one of sodium polyphosphate, sodium hexametaphosphate, sodium pyrophosphate and sodium polyacrylate.
[0034] Preferably, the first defoaming agent is selected from at least one of a mineral oil defoaming agent and a silicone defoaming agent.
[0035] Preferably, the first wetting agent is a polyoxyethylene ether wetting agent.
[0036] Preferably, the first film-forming aid is selected from at least one of ethylene glycol, propylene glycol, 12-dodecyl alcohol ester and stearic acid ester.
[0037] Preferably, the first thickener is selected from at least one of hydroxyethyl cellulose ether and hydroxypropyl methyl cellulose ether.
[0038] The method for preparing the thermal insulation layer comprises the following steps:
[0039] Add a formulated amount of water into a stirring kettle, then add a formulated amount of a first dispersant, a first wetting agent, and a first defoamer in sequence, and stir until they are completely dissolved; add a formulated amount of nano-alumina, nano-silicon dioxide, nano-fiber, nano-silver, a first hollow microbead, wood fiber, and silicate cement while stirring at 100-200 rpm, stir for 3-5 minutes to ensure that the materials do not clump, then disperse for 10-20 minutes while stirring at 650-750 rpm to ensure that the materials are evenly dispersed; finally, add a formulated amount of a first adhesive, a first film-forming aid, and a first thickener while stirring at 100-200 rpm, turn to 500-600 rpm to stir and disperse for 20-30 minutes, and obtain the material for the thermal insulation layer.
[0040] Preferably, the second hollow microspheres are ceramic hollow microspheres with a particle size distribution range of 1 to 100 μm, a D50 of 10 to 50 μm, a D90 of 15 to 35 μm, and a wall thickness of 1 to 2 μm.
[0041] Preferably, the particle size of the nano-alumina in the finishing layer is 200-500 nm, and the particle size of the nano-silicon dioxide is 500-800 nm.
[0042] Preferably, the colored sand in the finishing layer is marble or granite processed through multiple processes such as selection, crushing, grading and packaging, with a particle size distribution range of 100-300 μm, D50 of 150-250 μm and D90 of 120-270 μm, so that the finishing layer can simulate the texture and color of natural stone.
[0043] Adding nano-alumina and nano-silicon dioxide to the finishing layer improves the thermal insulation effect of the finishing layer. At the same time, by controlling the content and particle size of nano-alumina and nano-silicon dioxide in the thermal insulation layer and the finishing layer, the bonding strength between the finishing layer and the thermal insulation layer can also be enhanced; the second hollow microbeads can reflect more infrared light and invisible light, and because the second microbeads are hollow structures, they also have good thermal insulation effects.
[0044] Preferably, the second defoamer in the finishing layer is selected from at least one of a mineral oil defoamer and a silicone defoamer.
[0045] Preferably, the second dispersant in the finishing layer is selected from at least one of sodium polyphosphate, sodium hexametaphosphate, sodium pyrophosphate and sodium polyacrylate.
[0046] Preferably, the second film-forming aid in the finishing layer is selected from at least one of ethylene glycol, propylene glycol, alcohol ester dodecyl and stearic acid ester.
[0047] Preferably, the second wetting agent in the finishing layer is a polyoxyethylene ether wetting agent.
[0048] Preferably, the second thickener in the finishing layer is selected from at least one of hydroxyethyl cellulose ether and hydroxypropyl methyl cellulose ether.
[0049] The method for preparing the finishing layer comprises the following steps:
[0050] Add a formulated amount of water to a stirring kettle, then add a formulated amount of a second dispersant, a second defoamer, and a second wetting agent in sequence, and stir until completely dissolved; add a formulated amount of nano-alumina, nano-silicon dioxide, and a second hollow microsphere while stirring at 100-200 rpm, stir for 3-5 minutes to ensure that the materials do not clump, then disperse at 650-750 rpm for 10-20 minutes to ensure that the materials are evenly dispersed; finally, add a formulated amount of a second adhesive, a second film-forming aid, and a second thickener while stirring at 100-200 rpm, stir and disperse at 500-600 rpm for 20-30 minutes, add a formulated amount of colored sand, stir and disperse at 250-350 rpm for 20-30 minutes, and obtain the material for the finishing layer.
[0051] The preparation method of the building exterior wall thermal insulation system comprises the following steps:
[0052] S1. Apply an adhesive layer with a thickness of 0.5 to 2 mm on the exterior wall of the building;
[0053] S2. Apply a thermal insulation layer with a thickness of 0.8 to 3 mm on the dried adhesive layer;
[0054] S3. Apply a finishing layer with a thickness of 0.2 to 0.5 mm on the dried thermal insulation layer.
[0055] The present invention has the following beneficial effects:
[0056] The building exterior wall thermal insulation system of the present invention comprises an adhesive layer, a thermal insulation layer and a finishing layer, wherein the adhesive layer can improve the bonding strength between the thermal insulation layer and the building exterior wall; by controlling the particle size and content of the components in the thermal insulation layer and the finishing layer, a good stacking state can be formed in the thermal insulation layer and the finishing layer, and a good blocking rate for infrared light and ultraviolet light is achieved, thereby improving the thermal insulation effect; and some components in the adhesive layer, the thermal insulation layer and the finishing layer have the same or similar structures, so that the three have good compatibility and strong bonding ability, can prevent interlayer cracking, and ensure the thermal insulation effect of the thermal insulation system; in addition, nanomaterials, a second hollow microsphere, a second adhesive, and colored sand are combined in the finishing layer, so that its decorative effect is similar to that of marble and granite, thereby making the thermal insulation system have the advantages of strong decorativeness, wide applicability, water-based environmental protection, good stain resistance, long service life, and the like. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail in combination with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] Example 1
[0059] A building exterior wall thermal insulation system comprises an adhesive layer, a thermal insulation layer and a finishing layer.
[0060] The adhesive layer includes the following components in parts by weight:
[0061] 38 parts of pure acrylic emulsion, 49 parts of silicate cement, 35 parts of quartz sand, 5 parts of wood fiber, 46 parts of water, 1 part of sodium polyacrylate, and 1 part of dimethyl silicone oil.
[0062] The preparation method of the bonding layer material comprises the following steps:
[0063] Add the formulated amount of pure acrylic emulsion into the stirring kettle, stir at 150 rpm for 15 minutes, then add the formulated amount of silicate cement, quartz sand, wood fiber, water, sodium polyacrylate and second methyl silicone oil into the stirring kettle, stir and disperse at 700 rpm for 30 minutes to obtain the material for the bonding layer.
[0064] The thermal insulation layer comprises the following components in parts by weight:
[0065] 5 parts of nano-alumina, 5 parts of nano-silicon dioxide, 2 parts of nano-fiber, 5 parts of nano-silver, 2 parts of nano-ceramic hollow microspheres, 13 parts of wood fiber, 16 parts of Portland cement, 30 parts of pure acrylic emulsion, 30 parts of water, 1 part of hydroxyethyl cellulose ether, 1 part of sodium polyacrylate, 1 part of dimethyl silicone oil, 1 part of isomeric tridecanol polyoxyethylene ether, and 1 part of alcohol ester dodecahydrate.
[0066] The preparation method of the thermal insulation layer material comprises the following steps:
[0067] Add the formulated amount of water to the stirring kettle, then add the formulated amount of sodium polyacrylate, isomeric tridecyl alcohol polyoxyethylene ether, and dimethyl silicone oil in sequence, and stir until completely dissolved; add the formulated amount of nano-alumina, nano-silicon dioxide, nanofiber, nano-silver, nano-ceramic hollow microspheres, wood fiber, and silicate cement under stirring at 150rpm, stir for 5 minutes to ensure that the materials do not clump, then disperse for 12 minutes under stirring at 750rpm to ensure that the materials are evenly dispersed; finally, add the formulated amount of pure acrylic emulsion, alcohol ester twelve, and hydroxyethyl cellulose ether under stirring at 150rpm, turn to 550rpm and stir and disperse for 25 minutes to obtain the material for the thermal insulation layer.
[0068] The finishing layer includes the following components in parts by weight:
[0069] 3 parts of nano silicon dioxide, 3 parts of nano alumina, 13 parts of ceramic hollow microspheres, 55 parts of colored sand, 35 parts of pure acrylic emulsion, 35 parts of water, 1 part of dimethyl silicone oil, 1 part of sodium polyacrylate, 1 part of alcohol ester dodecahydrate, 1 part of hydroxyethyl cellulose ether, and 1 part of isomeric tridecanol polyoxyethylene ether.
[0070] The preparation method of the finishing layer material comprises the following steps:
[0071] Add the formulated amount of water to the stirring kettle, and then add the formulated amount of sodium polyacrylate, dimethyl silicone oil, and isotridecyl polyoxyethylene ether in sequence, and stir until completely dissolved; add the formulated amount of nano-alumina, nano-silicon dioxide, and ceramic hollow microspheres while stirring at 150rpm, stir for 5 minutes to ensure that the materials do not clump, and then disperse them while stirring at 650rpm for 20 minutes to ensure that the materials are evenly dispersed; add the formulated amount of pure acrylic emulsion, alcohol ester twelve, and hydroxyethyl cellulose ether, stir and disperse at 600rpm for 25 minutes, add the formulated amount of colored sand, stir at 300rpm for 30 minutes, and obtain the material for the finishing layer.
[0072] The preparation method of the building exterior wall thermal insulation system comprises the following steps:
[0073] S1. Apply a bonding layer with a thickness of 0.8 mm on the exterior wall of the building;
[0074] S2, coating a thermal insulation layer with a thickness of 1.5 mm on the dried adhesive layer;
[0075] S3. Apply a finishing layer with a thickness of 0.5 mm on the dried thermal insulation layer.
[0076] Example 2
[0077] Compared with Example 1, the main differences are:
[0078] The thermal insulation layer comprises the following components in parts by weight:
[0079] 10 parts of nano-alumina, 10 parts of nano-silicon dioxide, 5 parts of nano-fiber, 10 parts of nano-silver, 5 parts of nano-ceramic hollow microspheres, 13 parts of wood fiber, 16 parts of Portland cement, 30 parts of pure acrylic emulsion, 30 parts of water, 1 part of hydroxyethyl cellulose ether, 1 part of sodium polyacrylate, 1 part of dimethyl silicone oil, 1 part of isomeric tridecanol polyoxyethylene ether, and 1 part of alcohol ester dodecahydrate.
[0080] Example 3
[0081] Compared with Example 1, the main differences are:
[0082] The thermal insulation layer comprises the following components in parts by weight:
[0083] 7 parts of nano-alumina, 6 parts of nano-silicon dioxide, 3 parts of nano-fiber, 7 parts of nano-silver, 3 parts of nano-ceramic hollow microspheres, 13 parts of wood fiber, 16 parts of Portland cement, 30 parts of pure acrylic emulsion, 30 parts of water, 1 part of hydroxyethyl cellulose ether, 1 part of sodium polyacrylate, 1 part of dimethyl silicone oil, 1 part of isomeric tridecanol polyoxyethylene ether, and 1 part of alcohol ester dodecahydrate.
[0084] Example 4
[0085] Compared with Example 1, the main differences are:
[0086] The thermal insulation layer comprises the following components in parts by weight:
[0087] 7 parts of nano-alumina, 8 parts of nano-silicon dioxide, 3 parts of nano-fiber, 8 parts of nano-silver, 4 parts of nano-ceramic hollow microspheres, 13 parts of wood fiber, 16 parts of Portland cement, 30 parts of pure acrylic emulsion, 30 parts of water, 1 part of hydroxyethyl cellulose ether, 1 part of sodium polyacrylate, 1 part of dimethyl silicone oil, 1 part of isomeric tridecanol polyoxyethylene ether, and 1 part of alcohol ester dodecahydrate.
[0088] Example 5
[0089] Compared with Example 1, the main differences are:
[0090] The thermal insulation layer comprises the following components in parts by weight:
[0091] 7 parts of nano-alumina, 8 parts of nano-silicon dioxide, 3 parts of nano-ceramic fiber, 8 parts of nano-silver, 4 parts of nano-ceramic hollow microspheres, 10 parts of wood fiber, 16 parts of Portland cement, 30 parts of pure acrylic emulsion, 30 parts of water, 1 part of hydroxyethyl cellulose ether, 1 part of sodium polyacrylate, 1 part of dimethyl silicone oil, 1 part of isomeric tridecanol polyoxyethylene ether, and 1 part of alcohol ester dodecahydrate.
[0092] Example 6
[0093] Compared with Example 1, the main differences are:
[0094] The thermal insulation layer comprises the following components in parts by weight:
[0095] 7 parts of nano-alumina, 8 parts of nano-silicon dioxide, 3 parts of nano-ceramic fiber, 8 parts of nano-silver, 4 parts of nano-ceramic hollow microspheres, 15 parts of wood fiber, 16 parts of Portland cement, 30 parts of pure acrylic emulsion, 30 parts of water, 1 part of hydroxyethyl cellulose ether, 1 part of sodium polyacrylate, 1 part of dimethyl silicone oil, 1 part of isomeric tridecanol polyoxyethylene ether, and 1 part of alcohol ester dodecahydrate.
[0096] Example 7
[0097] Compared with Example 4, the main differences are:
[0098] The finishing layer includes the following components in parts by weight:
[0099] 2 parts of nano silicon dioxide, 2 parts of nano alumina, 10 parts of ceramic hollow microspheres, 55 parts of colored sand, 35 parts of pure acrylic emulsion, 35 parts of water, 1 part of dimethyl silicone oil, 1 part of sodium polyacrylate, 1 part of alcohol ester dodecahydrate, 1 part of hydroxyethyl cellulose ether, and 1 part of isomeric tridecanol polyoxyethylene ether.
[0100] Example 8
[0101] Compared with Example 4, the main differences are:
[0102] The finishing layer includes the following components in parts by weight:
[0103] 5 parts of nano silicon dioxide, 5 parts of nano alumina, 15 parts of ceramic hollow microspheres, 55 parts of colored sand, 35 parts of pure acrylic emulsion, 35 parts of water, 1 part of dimethyl silicone oil, 1 part of sodium polyacrylate, 1 part of alcohol ester dodecahydrate, 1 part of hydroxyethyl cellulose ether, and 1 part of isomeric tridecanol polyoxyethylene ether.
[0104] Example 9
[0105] Compared with Example 4, the main differences are:
[0106] The finishing layer includes the following components in parts by weight:
[0107] 4 parts of nano silicon dioxide, 4 parts of nano alumina, 13 parts of ceramic hollow microspheres, 55 parts of colored sand, 35 parts of pure acrylic emulsion, 35 parts of water, 1 part of dimethyl silicone oil, 1 part of sodium polyacrylate, 1 part of alcohol ester dodecahydrate, 1 part of hydroxyethyl cellulose ether, and 1 part of isomeric tridecanol polyoxyethylene ether.
[0108] Comparative Example 1
[0109] Compared with Example 9, the main differences are:
[0110] The thermal insulation layer comprises the following components in parts by weight:
[0111] 2 parts of nano-alumina, 2 parts of nano-silicon dioxide, 1 part of nano-ceramic fiber, 2 parts of nano-silver, 1 part of nano-ceramic hollow microspheres, 13 parts of wood fiber, 16 parts of Portland cement, 30 parts of pure acrylic emulsion, 30 parts of water, 1 part of hydroxyethyl cellulose ether, 1 part of sodium polyacrylate, 1 part of dimethyl silicone oil, 1 part of isomeric tridecanol polyoxyethylene ether, and 1 part of alcohol ester dodecahydrate.
[0112] Comparative Example 2
[0113] Compared with Example 9, the main differences are:
[0114] The thermal insulation layer comprises the following components in parts by weight:
[0115] 7 parts of nano-alumina, 8 parts of nano-silicon dioxide, 3 parts of nano-ceramic fiber, 8 parts of nano-silver, 4 parts of nano-ceramic hollow microspheres, 3 parts of wood fiber, 16 parts of silicate cement, 30 parts of pure acrylic emulsion, 30 parts of water, 1 part of hydroxyethyl cellulose ether, 1 part of sodium polyacrylate, 1 part of dimethyl silicone oil, 1 part of isomeric tridecanol polyoxyethylene ether, and 1 part of alcohol ester dodecahydrate.
[0116] Comparative Example 3
[0117] Compared with Example 9, the main differences are:
[0118] The building exterior wall insulation system does not have an adhesive layer.
[0119] The preparation method of the building exterior wall thermal insulation system comprises the following steps:
[0120] S1. Apply a 1.5mm thick insulation layer on the exterior wall of the building;
[0121] S2. Apply a finishing layer with a thickness of 0.5 mm on the dried thermal insulation layer.
[0122] Comparative Example 4
[0123] Compared with Example 9, the main differences are:
[0124] The finishing layer includes the following components in parts by weight:
[0125] 1 part of nano silicon dioxide, 1 part of nano alumina, 3 parts of ceramic hollow microspheres, 60 parts of colored sand, 35 parts of pure acrylic emulsion, 35 parts of water, 1 part of dimethyl silicone oil, 1 part of sodium polyacrylate, 1 part of alcohol ester dodecanol, 1 part of hydroxyethyl cellulose ether, and 1 part of isomeric tridecanol polyoxyethylene ether.
[0126] Comparative Example 5
[0127] Compared with Example 9, the main differences are:
[0128] The preparation method of the building exterior wall thermal insulation system comprises the following steps:
[0129] S1. Apply a bonding layer with a thickness of 0.2 mm on the exterior wall of the building;
[0130] S2, coating a thermal insulation layer with a thickness of 0.3 mm on the dried adhesive layer;
[0131] S3. Apply a finishing layer with a thickness of 0.2 mm on the dried thermal insulation layer.
[0132] The performance of the building exterior wall insulation systems of the above embodiments and comparative examples was tested according to JG / T 235-2014, GB / T2680-2021, and JG / T 24-2018. The test results are shown in the following table.
[0133] Table 1: Test data table of Examples 1 to 5
[0134]
[0135] Table 2: Test data table of Examples 6 to 9
[0136]
[0137]
[0138] Table 3: Comparative Examples 1 to 5 Test Data Table
[0139]
[0140] Comparing Examples 1 to 9 with Comparative Example 1, it can be seen from Tables 1, 2 and 3 that when the amount of nano-alumina, nano-silicon dioxide, nano-ceramic fiber, nano-silver and nano-ceramic hollow microspheres added to the thermal insulation layer is less than the formula amount, the thermal insulation performance (solar reflectance, near-infrared reflectance, hemispherical emissivity, solar reflectance change rate after pollution, solar reflectance change rate after artificial weather aging, vertical emissivity), bonding strength and water absorption of the building exterior wall thermal insulation system are all poor and cannot meet the technical requirements;
[0141] Comparing Examples 1 to 9 with Comparative Example 2, it can be seen from Tables 1, 2 and 3 that when the amount of wood fiber added to the insulation layer is less than the formula amount, the thermal insulation performance (solar reflectance, near-infrared reflectance, hemispherical emissivity, solar reflectance change rate after pollution, solar reflectance change rate after artificial weathering, vertical emissivity), bonding strength and water absorption of the insulation system are all poor and cannot meet the technical requirements;
[0142] Comparing Examples 1 to 9 with Comparative Examples 3 and 5, it can be seen from Table 1, Table 2 and Table 3 that when no adhesive layer is provided in the thermal insulation system, or when the adhesive layer and the thermal insulation layer are coated thinly, the thermal insulation performance (solar reflectance, near-infrared reflectance, hemispherical emissivity, solar reflectance change rate after pollution, solar reflectance change rate after artificial weathering, vertical emissivity), bonding strength, and water absorption are all poor and cannot meet the technical requirements;
[0143] Comparing Examples 1 to 9 with Comparative Example 4, it can be seen from Tables 1, 2 and 3 that when the amount of nano-silicon dioxide, nano-alumina and ceramic hollow microspheres added in the finishing layer is less than the formula amount, the difference between the finishing layer components and the insulation layer components is too large, resulting in poor thermal insulation performance (solar reflectance, near-infrared reflectance, hemispherical emissivity, solar reflectance change rate after pollution, solar reflectance change rate after artificial weather aging, vertical emissivity), bonding strength and water absorption of the insulation system, which cannot meet the technical requirements;
[0144] In summary, the building exterior wall thermal insulation system prepared by the method of the present invention has good thermal insulation effect and excellent water resistance and bonding strength.
Claims
1. A building exterior wall insulation system, characterized in that: It includes an adhesive layer, a thermal insulation layer and a finishing layer which are sequentially arranged from the wall surface to the outside of the wall; The thermal insulation layer comprises the following components in parts by weight: 5-10 parts of nano-alumina, 5-10 parts of nano-silicon dioxide, 2-5 parts of nano-fibers, 5-10 parts of nano-silver, 10-15 parts of wood fibers, 10-20 parts of silicate cement, 2-5 parts of first hollow microspheres, 25-35 parts of first adhesive, 20-35 parts of water, 0.5-1 part of first thickener, 0.5-1 part of first dispersant, 0.5-1 part of first defoamer, 0.5-1 part of first wetting agent, 0.5-1 part of first film-forming aid; The first adhesive is selected from at least one of pure acrylic emulsion and styrene acrylic emulsion; The finishing layer comprises the following components in parts by weight: 2-5 parts of nano silicon dioxide, 2-5 parts of nano aluminum oxide, 10-15 parts of second hollow microspheres, 45-65 parts of colored sand, 25-40 parts of second adhesive, 25-40 parts of water, 0.5-1 part of second defoamer, 0.5-1 part of second dispersant, 0.5-1 part of second film-forming aid, 0.5-1 part of second thickener, 0.5-1 part of second wetting agent; The second adhesive is selected from at least one of pure acrylic emulsion and styrene acrylic emulsion.
2. A building exterior wall insulation system according to claim 1, characterized in that: The adhesive layer comprises the following components in parts by weight: 30-40 parts of acrylic emulsion, 45-55 parts of Portland cement, 30-40 parts of quartz sand, 3-5 parts of wood fiber, 40-50 parts of water, 0.5-1.5 parts of the third dispersant, and 0.5-1.5 parts of the third defoamer; The acrylic emulsion is selected from at least one of pure acrylic emulsion and styrene acrylic emulsion.
3. A building exterior wall insulation system according to claim 1 or 2, characterized in that: The thickness of the bonding layer is 0.5-2 mm, the thickness of the thermal insulation layer is 0.8-3 mm, and the thickness of the finishing layer is 0.2-0.5 mm.
4. A building exterior wall insulation system according to claim 2, characterized in that: The silicate cement in the bonding layer is 42.5 grade ordinary silicate cement; the quartz sand has a particle size distribution range of 0.08-0.80 mm, a D50 of 0.25-0.30 mm, and a D90 of 0.18-0.40 mm.
5. A building exterior wall insulation system according to claim 2, characterized in that: The length of the wood fibers in the adhesive layer is 1 to 3 mm, and the diameter is 0.05 to 0.1 mm.
6. A building exterior wall insulation system according to claim 1 or 2, characterized in that: The particle size of the nano-alumina in the thermal insulation layer is 20-100nm, the particle size of the nano-silicon dioxide is 50-200nm, and the particle size of the nano-silver is 25-50nm.
7. A building exterior wall insulation system according to claim 1 or 2, characterized in that: The nanofibers in the thermal insulation layer are nanoceramic fibers, and the diameter of the nanoceramic fibers is 100-300 nm.
8. A building exterior wall insulation system according to claim 1 or 2, characterized in that: The first hollow microspheres in the thermal insulation layer are nano ceramic hollow microspheres with a particle size of 100-500 nm.
9. A building exterior wall insulation system according to claim 1 or 2, characterized in that: The length of the wood fiber in the thermal insulation layer is 0.5-1 mm, and the diameter is 0.02-0.05 mm.
10. A building exterior wall insulation system according to claim 1 or 2, characterized in that: The second hollow microspheres in the finishing layer are ceramic hollow microspheres with a particle size distribution range of 1 to 100 μm, a D50 of 10 to 50 μm, a D90 of 15 to 35 μm, and a wall thickness of 1 to 2 μm.
Citation Information
Patent Citations
A building exterior wall insulation system
CN103938740B